Experimental Study on the Effect of Single and Double Quenching-Tempering on the Mechanical Properties of AISI 1045 Steel - Syaipudin Anwar; Harnowo Supriadi; Nafrizal; Rizal Adi Saputra; Andree Agasy Nofma (Universitas Islam Malang, 2026)
This study examined the effects of quenching, single quenching–tempering (SQT), and double quenching–tempering (DQT) on the microstructure and mechanical properties of AISI 1045 medium-carbon steel (0.54% C, 0.32% Si, 0.65% Mn, 0.015% P, 0.0112% S, balance Fe). All specimens were heated to 850°C for 25 minutes and quenched in coconut oil at 100°C. Tempering was subsequently performed at 650°C for the SQT and DQT treatments. Hardness testing revealed that quenching produced the highest hardness value of 242.38 kg/mm² due to the formation of martensite. The SQT treatment reduced hardness to 198.46 kg/mm², indicating improved toughness while maintaining relatively high hardness. Further reduction in hardness was observed in the DQT-treated specimens, reaching 158.13 kg/mm², reflecting a more ductile and tougher microstructure. Impact properties were evaluated using the Charpy method. Heat-treated specimens exhibited significantly higher impact strength than the untreated material. The SQT process increased impact strength to 1.5792 J/mm², demonstrating the beneficial effect of tempering on toughness. The highest impact strength was achieved through DQT, reaching 1.8542 J/mm², indicating superior energy absorption capability. The results show that repeated quenching and tempering cycles effectively enhance the toughness of AISI 1045 steel, although accompanied by a reduction in hardness. Overall, DQT provided the best improvement in impact resistance and toughness among the heat treatment conditions investigated.